ChemInform Abstract: Synthesis of 2‐Trifluoromethyl Indoles via Visible‐Light Induced Intramolecular Radical Cyclization. Issue 37 (September 2015) - Dong, Xichang; Hu, Yumin; Xiao, Tiebo; Zhou, Lei
Abstract of N‐(2‐alkynylphenyl)trifluoroacetimidoyl chlorides